2021
DOI: 10.2196/32847
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Smartphone Apps for Cigarette Smoking Cessation: Results of a Serial Mediation Model From the iCanQuit Randomized Trial

Abstract: Background Engagement with digital interventions is a well-known predictor of treatment outcomes, but this knowledge has had limited actionable value. Instead, learning why engagement with digital interventions impact treatment outcomes can lead to targeted improvements in their efficacy. Objective This study aimed to test a serial mediation model of an Acceptance and Commitment Therapy (ACT) smartphone intervention for smoking cessation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Since participants were not engaged in other smoking cessation treatment, these findings are promising for the efficacy of iCanQuit as a stand-alone approach for smoking cessation. Furthermore, results from this study showed a significant serial mediation effect of the iCanQuit intervention, through increased acceptance of smoking cues [29 ▪▪ ]. This advances the existing evidence by being one of the only studies to unveil mechanistic effects of a mHealth intervention.…”
Section: Smoking Cessation Mhealth Appssupporting
confidence: 57%
“…Since participants were not engaged in other smoking cessation treatment, these findings are promising for the efficacy of iCanQuit as a stand-alone approach for smoking cessation. Furthermore, results from this study showed a significant serial mediation effect of the iCanQuit intervention, through increased acceptance of smoking cues [29 ▪▪ ]. This advances the existing evidence by being one of the only studies to unveil mechanistic effects of a mHealth intervention.…”
Section: Smoking Cessation Mhealth Appssupporting
confidence: 57%
“…Two potential reasons why iCanQuit's, but not QuitGuide's, second trajectory group had higher quit rates are most likely due to the content and structure of the iCanQuit app. Regarding content, we have published multiple studies showing that the effect of iCanQuit (but not QuitGuide) on smoking cessation was mediated by ACT-based processes of acceptance of internal cues to smoke (ie, sensations, thoughts, and emotions) [35,[45][46][47][48]. The differences in content, with iCanQuit focused on ACT versus QuitGuide focused on standard USCPG content [49], suggest that 4 weeks of engaging with ACT content that targets acceptance of internal cues is effective at improving quit rates.…”
Section: Use Trajectories and Health Outcomesmentioning
confidence: 99%
“…Previous studies have demonstrated that ACT-based interventions promote smoking cessation by teaching adults who smoke to accept their cravings to smoke and let these cravings pass without smoking [6][7][8][9][10][11][12][13][14][15]. Compared to standard approaches for tobacco cessation, such as the USCPG that teaches avoidance of cravings, ACT-based processes teach people to observe and accept emotions and cravings that cue smoking.…”
Section: Introductionmentioning
confidence: 99%
“…We published a large ( n = 2415) randomized controlled trial (RCT) to determine the efficacy of a smartphone app for smoking cessation (iCanQuit) based on acceptance and commitment therapy (ACT) compared with a National Cancer Institute (NCI) smoking cessation app (QuitGuide) based on the US Clinical Practice Guidelines (USCPG) [5]. Previous studies have demonstrated that ACT‐based interventions promote smoking cessation by teaching adults who smoke to accept their cravings to smoke and let these cravings pass without smoking [6–15]. Compared to standard approaches for tobacco cessation, such as the USCPG that teaches avoidance of cravings, ACT‐based processes teach people to observe and accept emotions and cravings that cue smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation